A planet in transition: The onset of plate tectonics on Earth between 3 and 2 Ga? - Kent C. Condie (Geoscience Frontiers, 2018)
Many geological and geochemical changes are recorded on Earth between 3 and 2 Ga. Among the more important of these are the following: (1) increasing proportion of basalts with “arc-like” mantle sources; (2) an increasing abundance of basalts derived from enriched (EM) and depleted (DM) mantle sources; (3) onset of a Great Thermal Divergence in the mantle; (4) a decrease in degree of melting of the mantle; (5) beginning of large lateral plate motions; (6) appearance of eclogite inclusions in diamonds; (7) appearance and rapid increase in frequency of collisional orogens; (8) rapid increase in the production rate of continental crust as recorded by zircon age peaks; (9) appearance of ophiolites in the geologic record, and (10) appearance of global LIP (large igneous province) events some of which correlate with global zircon age peaks. All of these changes may be tied directly or indirectly to cooling of Earth's mantle and corresponding changes in convective style and the strength of the lithosphere, and they may record the gradual onset and propagation of plate tectonics around the planet. To further understand the changes that occurred between 3 and 2 Ga, it is necessary to compare rocks, rock associations, tectonics and geochemistry during and between zircon age peaks. Geochemistry of peak and inter-peak basalts and TTGs needs to be evaluated in terms of geodynamic models that predict the existence of an episodic thermal regime between stagnant-lid and plate tectonic regimes in early planetary evolution.